Affinity modulation of small-molecule ligands by borrowing endogenous protein surfaces - Briesewitz, Roger (The National Academy of Sciences, 1999)
A general strategy is described for improving the binding properties of small-molecule ligands to protein targets. A bifunctional molecule is created by chemically linking a ligand of interest to another small molecule that binds tightly to a second protein. When the ligand of interest is presented to the target protein by the second protein, additional protein–protein interactions outside of the ligand-binding sites serve either to increase or decrease the affinity of the binding event. We have applied this approach to an intractable target, the SH2 domain, and demonstrate a 3-fold enhancement over the natural peptide. This approach provides a way to modulate the potency and specificity of biologically active compounds.